Synthesis and characterization of tartaric acid modified starch from native sago starch - Lim, Lih Shan (Universiti Malaysia Sarawak (UNIMAS), 2011)
This research aimed to synthesize starch tartarate and characterize the physico-chemical properties of starch tartarate. Starch tartarate was synthesized by esterification reaction of native sago starch and tartaric acid. The physical and chemical properties of resulting starch tartarate were characterized. Throughout the screening of esterification, only solvent system only using dimethyl sulphoxide (DMSO) at 100 degree Celsius and with the presence of 2-dimethylamino pyridine (DMAP) as catalyst gave the carbonyl group between starch and tartaric acid.